Operational discipline in practice - Rashid, M.I. (John Wiley and Sons Inc, 2021)
A general guideline to improve operational discipline is required. Operational discipline can be improved with simple things such as floor level meeting (FLM), job cycle check (JCC), risk assessment (RA), daily safety audit (DSA), consequence analysis (CA), mechanical integrity (MI), incident investigation (II), management of change (MOC), behavior observation (BO), pre-start up safety reviews (PSSR), process hazard analysis (PHA), job risk assessment (JRA), quantitative risk assessment (QRA), and process safety management (PSM) implementation. This article presents risks identified from floor level meetings, steps for job cycle check and risk sensitivity and procedure for daily safety audit and behavior observation audit. Consequence analysis, pre-start up safety review and why tree analysis are discussed for improving operational discipline. Inclusion of consequence analysis in work instructions is discussed. Procedure for accident investigation is elaborated by investigating trainee unit shift engineer (USE) burning injury accident and why tree diagram is constructed and findings and recommendations are provided. PHA techniques (HAZOP, Failure Mode and Effect Analysis) methodology is presented to enhance operational discipline. This article is especially for those industries which are located in countries where PSM implementation is not mandatory and they are lacking in operational discipline. Â© 2020 American Institute of Chemical Engineers